2013
DOI: 10.1016/j.neuroscience.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Responses of brain and behavior to changing day-length in the diurnal grass rat (Arvicanthis niloticus)

Abstract: Seasonal affective disorder (SAD) is a major depressive disorder that reoccurs in the fall and winter when day-lengths get short. It is well accepted that day-length is encoded by the principal circadian clock located in the suprachiasmatic nucleus (SCN), but very little is known about day-length encoding in diurnal mammals. The present study utilized the grass rat, Arvicanthis niloticus, to investigate how the circadian system responds to photoperiodic changes in a diurnal mammal that shows day-length depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 47 publications
4
44
0
Order By: Relevance
“…Using the diurnal Nile grass rats, we and others have observed depression- and anxiety-like behaviors in winter-like lighting conditions, i.e. short photoperiods [4, 18] or daytime dim lighting [7, 17]. Furthermore, we found that hypothalamic neurons containing the neuropeptide orexin are likely to play a role in mediating the effects of light on mood and anxiety.…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…Using the diurnal Nile grass rats, we and others have observed depression- and anxiety-like behaviors in winter-like lighting conditions, i.e. short photoperiods [4, 18] or daytime dim lighting [7, 17]. Furthermore, we found that hypothalamic neurons containing the neuropeptide orexin are likely to play a role in mediating the effects of light on mood and anxiety.…”
Section: Introductionsupporting
confidence: 51%
“…The number of TH-ir cells in the antagonist-treated group was comparable to those observed in DLD or SP animals. Furthermore, animals in these three comparable pro-depression conditions show increased depression-like behaviors compared to those in BLD group [4, 7, 17, 18]. The results indicate that the hypothalamic DA cells are related to the prevailing affective state.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…One form of depression that is susceptible to changes in day length is seasonal affective disorder, which is at least partially based on photoperiodic alterations of the circadian system (26). A recent study using a day-active rodent model suggests a link between depressive-like behaviors and the photoperiodic responsiveness of the circadian clock (27). Although there is still insufficient evidence on the neurobiological mechanisms underlying seasonal affective disorder, altered GABAergic signaling in the SCN neuronal network should be considered a potential contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…Four weeks of a 12 h/12 h light/dark cycle under dim illumination conditions (50 lux/1 lux) attenuated indices of serotonin signaling in the dorsal raphe nucleus in grass rats (A. niloticus) [34]. Three weeks of a short photoperiod (8 h/16 h light/dark cycle) induced lower brain levels of serotonin and its precursor l-tryptophan in C57BL/6J mice [35].…”
Section: Rhythms Of Plasma Levels Of Corticosterone Melatonin and Nmentioning
confidence: 95%